Reformulação curricular do curso de Ciências Contábeis na Universidade Estadual do Sudoeste da Bahia, a partir do olhar dos concluintes do curso do ano de 2012 - Araújo, Manoel Antonio Oliveira (2014)
This thesis aims to study the reformulation of the course in Accounting from the State University of Southwest Bahia in view of the graduates of the year 2012. This study is theoretically grounded in the curriculum scholars and Accounting as Apple, Sacristán, Tardif, Iudícibus, Masetto, Gonçalves, Abramowicz, Stake, among others. The Accounting course in UESB is the setting in which the study takes place. Their graduates and their documents (Teaching and Governing Law Project) are studied. The first underwent completing a questionnaire with ten questions that functioned as the instrument that raised the data tabulated by the technique of content analysis. Documentary analysis was also used as a technique for studying the above - mentioned documents. The category indicated in the study, with the highest incidence was Curricular Redesign who received specific treatment in the work of academic and scientific nature. This category is called work and has an emphasis on in the conceptualization and analysis. What are points, in fact, is that the course requires reformulation of the current curriculum, better training of their teachers, the appropriate educational infrastructure to achieve the prescribed curriculum for the course, special attention to professional character expected by students in your formation